Islamic Education Budget Management in the Time of The Prophet Muhammad SAW - Wulan Sari; Disniarti Disniarti; Yushinta Yushinta; Moh. Jawahir; Mutyati Mutyati (Innovative: Journal Of Social Science Research, 2023)
This study aimed to determine how Islamic education financing was managed during the time of the Prophet Muhammad SAW. The research method used was a literature review by looking for previous research results in articles and books, then analyzing and finding new concepts in understanding education financing management during the Prophet Muhammad SAW. Based on the analysis of the results of the Literature study, it is known that the control of the Islamic education budget during the time of the Prophet Muhammad was carried out very well and was organized. The management of the Islamic education budget at that time was based on the principles of fairness, transparency, and accountability. Funds are managed very well and transparently, and funds are not misused. Islamic religious education is carried out by direct teaching students face-to-face or classically, and the management of the education budget is well-planned and structured. These principles can be good examples of Islamic education budgets today. By applying the principles of fairness, transparency, and accountability, as well as by teaching students face-to-face or classically, it is hoped that the quality of Islamic education will increase. Therefore, the Islamic education budget management during the Prophet Muhammad SAW can be a reference for policymakers and educators in today's control of the Islamic education budget.